The Embodied Narrative Nature of Learning: Nurture in School. Issue 2 (June 2016) - Delafield‐Butt, Jonathan T.; Adie, Jillian
ABSTRACT: Learning is participatory and embodied. It requires active participation from both teacher and learner to come together to co‐create shared projects of discovery that allow meaning to unfold and develop between them. This article advances theory on the intersubjective and embodied nature of cognition and meaning‐making as constituted by co‐created narrative units. Learning within embodied narrative episodes incorporate affective, energetic, and intentional components to produce schemas of engagement that structure knowledge and become units held in memory. We examine two cases of nonverbal narrative patterns of engagement between teacher and child within Nurture Group practice, a special pedagogy that attunes to the affects and interests of children. Analysis of these cases reveal patterns that established shared rhythm, affect, and body movement between teacher and child, which, on completion, generated shared joy and learning. Thus, we identify an embodied, co‐created narrative structure of embodied cognition essential for learning and participatory meaning‐making.